From Guard to Decoy: a new model for perception of plant pathogen effectors. - van der Hoorn, R; Kamoun, S (2008)
The Guard Model for disease resistance postulates that plant resistance proteins act by monitoring (guarding) the target of their corresponding pathogen effector. We posit, however, that guarded effector targets are evolutionarily unstable in plant populations polymorphic for resistance (R) genes. Depending on the absence or presence of the R gene, guarded effector targets are subject to opposing selection forces (1) to evade manipulation by effectors (weaker interaction) and (2) to improve perception of effectors (stronger interaction). Duplication of the effector target gene or independent evolution of a target mimic could relax evolutionary constraints and result in a decoy that would be solely involved in effector perception. There is growing support for this Decoy Model from four diverse cases of effector perception involving Pto, Bs3, RCR3, and RIN4. We discuss the differences between the Guard and Decoy Models and their variants, hypothesize how decoys might have evolved, and suggest ways to challenge the Decoy Model.